Vaccines for older adults : current practices and future opportunities - Weinberger, Birgit (Basel : Karger, 2020)
Many infectious diseases are more frequent and are associated with high morbidity and mortality in older adults. Vaccination is the most efficient strategy to prevent infections, and older adults are an important target population for vaccination in order to promote health in this age group. Age-related changes in the immune system as well as other factors, such as comorbidities, obesity or frailty, influence vaccine-induced immune responses in old age. Awareness that vaccines developed for children might not be optimal for adults, and particularly for the older population, has only arisen in the recent past. Vaccination against influenza, pneumococcal disease, and herpes zoster is specifically recommended for older adults in many countries, and various strategies have been pursued in order to optimize these vaccines. However, there are still many pathogens, which severely affect the older population, but for which no vaccines are currently available. Extensive research and development are ongoing to further improve existing vaccines and to design novel vaccines in order to provide protection for this vulnerable age group. In order to exploit the full protective potential of vaccines it is essential to improve vaccine uptake and overcome vaccine hesitancy by providing information and education to stakeholders, health care professionals, and the general public. This book is relevant for researchers working on age-related changes in the immune system or on vaccine development, for health care professionals treating older patients, and for the stakeholders and decision makers involved in vaccination recommendations and implementation.
Keywords: ANCIANOS; VACUNACIÓN; ENVEJECIMIENTO -- ASPECTOS INMUNOLÓGICOS